Evaluating UP Mindanao's Socialized Tuition and Financial Assistance Program (STFAP) information sheet a communication plan - Caballero, Iva Barbara B.
Socialized Tuition and Financial Assistance Program(STFAP) or Iskolar ng Bayan Program was designed for UP students to benefit from discounted tuition fees based on their financial needs and capacity to pay. However, the Office of Student Affairs(OSA) has difficulty in disseminating information to potential students who are from remote areas. Hence, this study aims to find a medium that would inform incoming freshmen students of UP Mindanao, especially from remote areas, encouraging them to enroll in the university and create a communication plan for it. The researcher used survey and document review to gather information about the current state of STFAP's communication practices. The respondents of her survey were students under STFAP for second semester, AY 2011-2012. Survey questionnaires were distributed and gathered by OSA. The researcher analyzed and evaluated the STFAP's information sheet for incoming freshmen student this AY 2012-2013 and summarized her findings by using a Communication Practice Matrix. The research findings showed that STFAP's communication practices have already determined their vision, goal and target audiences. However, they have a lot of communication practices that they have not exercised. Thus, STFAP's communication plan generally lacked emphasis in the areas of implementation, and support and integration. Media Richness Theory was used in this study to be base line information on how a media could be considered rich. The theory states that a medium can only be rich if it eliminates uncertainty and equivocality by providing multiple cues at the same time and provides immediate feedback. Letters or unaddressed documents belong to leaner form of medium. However, the theory also states that there are certain medium that are applicable in certain situation or given task. This was proven true by the results of this study's communication audit. Survey showed that the respondents preferred letter to reach potential applicants, especially those from remote areas. Although letters could only relay and give minimal feedback and could not tailor its message to fit to its audiences, it was still the most efficient tool to reach its target audience. The location of the target audience must also be considered when choosing the medium to be used in a communication act. Letters therefore are the best communication tool based on its target audience. Hence, these were the areas the researcher addressed in her communication plan
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication